Active site-directed alkylation of Na+-K+-ATPase by digitalis sulphonate derivatives of different lipophilicity. - Fricke, U. (Nature Publishing Group, 1981)
1 Sulphonate derivatives of k-strophanthidin and digitoxigenin were tested as active site-directed labels of Na+-K+-adenosine triphosphatase (Na+-ATPase) from guinea-pig heart. 2 Lipophilicity ranged between P = 93 for strophanthidin-3-tosyloxy-acetate (STA) and P = 3028 for digitoxigenin-3-tosyloxy-acetate (DTA). 3 Although the alkylating moiety of STA and DTA was identical, the reversibility of Na+-K+-ATPase inhibition varied appreciably (82% and 35% respectively). 4 It is concluded that lipophilicity contributes considerably to the irreversible binding of alkylating cardiotonic steroids to myocardial Na+-K+-ATPase.